PROBLEMS OF ORGANIZING THE PROCESS OF INDEPENDENT EDUCATION IN CHEMISTRY IN HIGHER MILITARY EDUCATION INSTITUTIONS - Islamova Maftuna Sharofiddinovna, (Journal of new century innovations, 2023)
Abstract. This article describes the current state of independent preparation and organization of the independent educational process of cadets of the higher military education system, and the problems of improving the effectiveness of the educational process.